Upaya Meningkatkan Hasil Belajar Siswa Dengan Menerapkan Pendekatan Kontekstual Dalam Pembelajaran IPA Pada Materi Pokok Bioteknologi di Kelas XI-1 SMP Negeri 5 Stabat TP.2016/2017 - Rusli Rusli (BEST Journal (Biology Education, Sains and Technology), 2018)
Drs. Rusli, M.Pd., NIP. 196809302000121001, Master of SMP Negeri 5 Stabat, "Efforts to Improve Student Learning by Implementing Contextual Approach in Science Learning on Basic Matter of Biotechnology in Class IX-1 SMP Negeri 5 Stabat T.P. 2016/2017 ". Problem formulation: Is the application of contextual learning can improve student learning outcomes on science learning biotechnology main subject in class IX-1 SMP Negeri 5 Stabat T.P. 2016/2017. The purpose of this research is to know the improvement of student learning outcomes through the application of contextual approach on science learning biotechnology main subject in class IX-1 SMP Negeri 5 Stabat T.P. 2016/2017. The research procedure is carried out through two cycles with four stages: 1) planning; 2) action; 3) observation; 4) reflection; The unresolved problem is reflected as the teaching improvement material of the next cycle. The results of the classroom action research show the students' learning outcomes by applying contextual approaches have increased. This is seen in the average grade 74 (incomplete category) in the first cycle to 83 (complete category) in cycle II and the percentage of learning completeness classically increased from 53% in the first cycle to 87.5% in cycle II